Identidades culturais e emergência do nacionalismo angolano (c. 1885- c. 1930) - Gonçalves, António Custódio (Africana Studia, 2020)
This article analises the nature and emergence of the Angolan nationalism, between 1885 an 1930. ln the fírst part, the cultural and national identities are defined as processus and strategies. ln the second part, the author analises the fundamental forms of expression of these identities.